2009
DOI: 10.1097/mpg.0b013e31818550de
|View full text |Cite
|
Sign up to set email alerts
|

AIRE Gene Analysis in Children With Autoimmune Hepatitis Type I or II

Abstract: The present report describes AIRE gene analysis in 25 children with autoimmune hepatitis type I or II. The heterozygous transversion c.961C > G (p.Ser278Arg) located in exon 7 was identified in 4 patients with autoimmune hepatitis type I, and mostly in those presenting with a positive family history for autoimmune diseases. In this subgroup of patients, the allelic frequency of this polymorphic variant was at least 3-fold higher than in healthy controls. These results suggest that heterozygous AIRE gene mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 15 publications
0
11
0
1
Order By: Relevance
“…The role of AIRE1 heterozygote state in the development of AIH remains to be established. AIRE1 mutations have been reported in 3 children with severe AIH type 2 and extrahepatic autoimmune manifestations [13] and in 4 children with AIH type 1 and a family history of autoimmune disease [14].…”
Section: Geneticsmentioning
confidence: 99%
“…The role of AIRE1 heterozygote state in the development of AIH remains to be established. AIRE1 mutations have been reported in 3 children with severe AIH type 2 and extrahepatic autoimmune manifestations [13] and in 4 children with AIH type 1 and a family history of autoimmune disease [14].…”
Section: Geneticsmentioning
confidence: 99%
“…It has been noticed that several autoimmune disorders, such as vitiligo [10], autoimmune hepatitis [11], type 1 diabetes mellitus [12], myasthenia gravis [13] and systemic sclerosis [14], might be affected by the genetic variability of AIRE gene. A recent GWA study in Japanese population has been identified two SNPs, rs2075876 and rs760426, in the AIRE gene was significant associated with RA risk [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, unlike PBC and PSC, more detailed analysis using genome‐wide association studies of adequate size are not completed; thus, there are only very limited data beyond HLA candidate gene studies . One interesting exception has been the occurrence of AIH in children that bear the AIRE gene mutation, but these data and the analogy appear to be more the exceptions than the rule . Studies of twins have proven to be an exceedingly important resource to distinguish the relative role of genetics and environment, allowing quantification of risk based on comparisons of disease concordance between monozygotic and dizygotic twins but the relative infrequency of twinning in AIH has made such analysis problematic and data are limited to isolated case reports …”
mentioning
confidence: 99%